Assessment of the Geographical Factors Contributing to the Occurrence of the Flood and Flash Flood in Şanlıurfa on March 15, 2023 - Mustafa Recep İrcan; Neşe Duman (Doğal Afetler ve Çevre Dergisi)
Floods and flash floods are among the natural disasters that frequently occur in the world and have high destructive power. This study was prepared to evaluate the geographical factors that are effective in the formation of the flood and flash floods that occurred in Şanlıurfa on 15 March 2023 and 16 people lost their lives. In the study prepared for this purpose, the boundary of the research area was determined by hydrology analysis using ArcGIS for Desktop 10.5 software. With this analysis, lithology, slope and precipitation maps of the determined river basins (Karakoyun, Cavsak and Karaköprü-Sırrın Creeks) were produced. Within the scope of geographical evaluation, physical (lithological, geomorphological, climatological) and human factors have been considered one by one and examined under separate headings. Within the scope of physical factors, lithological, geomorphological and climatological characteristics of the area were examined. Within the scope of human factors, the effects of the stream beds in the basin on flood and flash flood generation were evaluated by photographing the field studies. According to the results, there is a topography where the elevation and slope decrease from north to south in the study area. It was determined that the saturation of the soil in the field with water in winter and the wrong interventions made to the stream bed caused a large part of the water to overflow from the stream beds with the torrential rainfall (119 mm in one day in total) on 15 March 2023, and the flood event along the slope in the field turned into a disaster and caused loss of life and property.